How Different Is Japanese Corporate Finance? An Investigation of the Information Content of New Security Issues - Kang, Jun-Koo; Stulz, René M. (Review of Financial Studies, 1996)
This paper studies the shareholder wealth effects associated with 875 new security issues in Japan from January 1, 1985 to May 31, 1991. The sample includes public equity, private equity, rights offerings, straight debt, warrant debt and convertible debt issues. Contrary to the U.S., the announcement of convertible debt issues is accompanied by a significant positive abnormal return of 1.05%. The announcement of equity issues has a positive abnormal return ofO.45%, significant at the 0.10 level, but this positive abnormal return can be attributed to one year in our sample and is offset by a negative issue date abnormal return of -1.01%. The abnormal returns are negatively related to firm size, so that for equity issues (but not for convertible debt issues), large Japanese firms have significant negative announcement abnormal returns. Our evidence is consistent with the view that Japanese managers decide to issue shares based on different considerations than American managers.